Predicting Repeated Child and Adolescent Residential Treatment Placements. Issue 4 (2nd October 2019) - Izmirian, Sonia C.; Milette-Winfree, Matthew; Jackson, David S.; Mueller, Charles W.
ABSTRACT: Repeated child and adolescent mental health residential treatment placements are important given such patterns can indicate inefficient and costly services, system of care imbalances and/or earlier treatment failure. Identifying factors that predict subsequent residential treatment placement at the same or more restrictive level of care can help the field consider assessment and intervention approaches to lessen multiple placements. The current study examined predictors of youth returning to the same or higher (more restrictive) level of care (vs. those who were successfully transitioned to home-based services) after an initial episode of community-based residential treatment. Although multiple variables predicted subsequent residential treatment placement, when entered together in a multiple logistic regression, younger age, the presence of an internalizing diagnosis (often with one or more externalizing diagnoses), rural facility location, and an unsuccessful discharge status from the initial residential treatment placement predicted greater likelihood of subsequent placement. Research and practice implications are discussed.